Early Modern Nautical Charts of the Adriatic Sea (Springer Nature, 2025)
This Open Access book provides a comprehensive and multi-layered understanding of the development of Adriatic Sea nautical cartography from its beginnings in the late Middle Ages to the implementation of geodetic and hydrographic surveys in the early nineteenth century. During the early modern period, the importance of nautical charts exceeded mere navigational purpose as they also became a medium for conveying an extensive array of socioeconomic information and messages. The authors examine how the geographical characteristics and social elements of the Adriatic Sea and its surroundings were observed, understood, and cartographically represented in accordance with contemporary scientific, technological, socioeconomic, cultural, or political frameworks using various phenomenological viewpoints and methodological techniques. Since the Adriatic Sea has historically functioned as a smaller-scale version of the Mediterranean, its contents transcend its geographical boundaries and are also broadly applicable to other Mediterranean regions.